Hicrî İlk Üç Asır Özelinde Sened ve Metin Kritiği Bağlamında Gurabâ Rivayetinin Değerlendirilmesi - Murat Gökalp (Dini Araştırmalar, 2015)
While the resources of early three centuries A.H include rarely The Narrative of Guraba, it has been attracted attention that the later period resources contain it rather frequently. We have a opinion that this narrative -apart from its weak from the perspective of isnad- is not word of the Prophet in point of its text